Fresh water quality as an essential component for a better quality of life: a study of intra and peri-domiciliary fresh water system in Morada Anchieta Park ward, RJ: DOI: 10.15343/0104-7809.200731.3.6 - Cynamon Cohen, Simone (2007)
For studying the adequacy of domestic equipment and systems, the project was designed to evaluate the quality of the watersupply system in the community, since there is an infrastructural precariousness in precarious areas of the urban peripheries. We observed theinexistence of a specific and systematic governmental and communitarian action for guiding on the correct storage means and the use of waterby people, putting their health in great danger; we thus emphasize the importance of studies on the quality of water in the non-official wardknown as Morada Anchieta Park. As a result of the research it was possible correlate the bad quality of water, either as supplied supplying andused, with the incidence of water-propagated diseases. Data on health of the research were collected in Carlos Chagas Hospital which takescare of the local population. A diagnosis was then formulated for the area in question. This diagnosis served as a subsidy in the elaboration ofproposals for actions aiming the physical improvement of the domiciliary system and as a basis for works of education for health and environmentaleducation. We point out the relevance of the said project in its relationship to a detailed study of the intra- and peri-domiciliary watersystem in non-official wards as a methodological proposal of education in health in similar areas and as a subsidy to public managers regardingplanning and action in future interventions.